PERAN KOMITMEN ORGANISASIONAL DALAM MEMEDIASI EFEK STRES KERJA, LMX DAN PERSEPSI DUKUNGAN ORGANISASIONAL PADA KUALITAS PELAYANAN (Studi pada Karyawan dan Pelanggan Industri Perhotelan di Surakarta) - SUHARYOKO SUHARYOKO (JURNAL WIDYA GANECWARA, 2017)
The purpose of this research were (1) to test the effect of work stress on organizational commitment. (2) Test the effect of LMX on organizational commitment. (3) Test the influence of POS on organizational commitment. (4) Test the effect of organizational commitment on service quality. (5) Test the mediating effect of organizational commitment on the influence of work stress, LMX, POS and service quality. This research was conducted in the Surakarta city hospitality industry. The population in this study were all front liner employees and customers from 3 hotels in Surakarta, namely Aston Hotels, Megaland Hotels, and Sunan Hotels with 145 employees. In this study researchers used 107 respondents as samples taken from 3 hotel industries in Surakarta City. The results found that Job Stress (job stress), member exchange leaders (LMX) and perceptions of organizational support (POS) of employees in the hospitality industry in Surakarta City had an influence on organizational commitment variables. Organizational commitment mediates the negative influence of Job Stress on service quality, while organizational commitment mediates the positive influence of member exchange leaders (LMX) and perceptions of organizational support on service quality.